Corporate environmental responsibility in investor-state dispute settlement : the unexhausted potential of current mechanisms / Tomoko Ishikawa, Nagoya University, Japan. - Ishikawa, Tomoko (Lawyer) (Cambridge University Press, 2023)
This book explores the potential of the current investor-state dispute settlement (ISDS) mechanism to materialise the responsibility of foreign investors through the states' counterclaims and defences at the jurisdictional, merits, and quantum phases. In doing so, it seeks to incorporate the recent developments of ISDS in both international and domestic laws of certain jurisdictions on corporate responsibility, including the parent company's due diligence and legal effects of corporations' voluntary commitments. The book also reflects the interests and perspectives of the victims who suffered loss and injury due to investors' conduct. The author demonstrates that the current system does have the inherent potential to advance responsible investment, even though reforms are needed to overcome its limitations. Fully utilising this potential to reflect investor responsibility in IIA-based dispute settlement mechanisms will help to develop practices based on greater due diligence and responsible business conduct.